Can Trade Benefit Natural Resources under Population Growth? The Role of Manufacturing's Returns to Scale - Maurice Schiff (Global Labor Organization (GLO), 2025)
I examine whether trade can improve the impact of population growth on natural resources (NR) and welfare over time. Under autarky, population growth results in NR and welfare collapse over time for any value of the returns to scale in the manufacturing sector, ϕ. Under trade, NR and welfare are unchanged (increase) (collapse) over time for ϕ = (>)(<)1 - though the decrease in welfare under ϕ < 1 is dampened relative to autarky. Thus, countries experiencing rapid population growth may benefit from opening up to trade.
Keywords: F16; F18; Q27; Q56; 330; Population growth; Renewable natural resources (NR); Trade vs autarky; Impact on NR and welfare